2013
DOI: 10.1097/meg.0b013e3283590a2a
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral biliary drainage for malignant hilar obstruction using the ‘stent-in-stent’ method with a Y-stent

Abstract: With the development of new devices and increased technical experience, there were better outcomes during the late period compared with the early period. Endoscopic bilateral metal stenting using a Y-stent is an attractive option for the palliative treatment of malignant hilar obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Although the extent of liver drainage remains unclear in cases of malignant hilar obstruction, bilateral biliary drainage has become generally accepted in recent studies [5,8,10,11,15]. New devices and various techniques for bilateral metallic stent placement across the hilar malignancy have been reported, including T-configured, Y-configured, and crisscross-configured dual stent placement [3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the extent of liver drainage remains unclear in cases of malignant hilar obstruction, bilateral biliary drainage has become generally accepted in recent studies [5,8,10,11,15]. New devices and various techniques for bilateral metallic stent placement across the hilar malignancy have been reported, including T-configured, Y-configured, and crisscross-configured dual stent placement [3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have described new devices and various techniques for bilateral bare metallic stent placement across the hilar malignancy, including T-configured [3][4][5][6], Y-configured [5][6][7][8], and crisscross-configured dual stent placement [5,9]. Moreover, successful use of covered stent was also reported in patients with malignant hilar biliary obstruction to provide durable stent patency without tumor ingrowth [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Stent occlusion rates are usually between 25% and 39%. [43][44][45][46] Cholecystitis (28% late and 9% early) and cholangitis (16% late and 6% early) are reported complications of Y-stents. 47 Another stent without wide mesh in the middle was evaluated in 35 patients and demonstrated 94% placement success rate, mean patency of 150 days and very low rate of cholangitis (6%).…”
mentioning
confidence: 99%
“…70 They used an open weave stent, allowing for more flexibility in aligning this area at the hilum. 70 The weave is designed to tighten, thereby increasing radial force to maintain cannulation. Kim et al showed that these stents had a stent-in-stent placement of 87%, with cholangitis reported in 1.5% of patients.…”
mentioning
confidence: 99%
“…The Ystent bilateral technique is a viable option to treat malignant hilar obstruction. 10,70 In 2010, Chahal et al deployed bilateral SEMS with a stent-in-stent approach. 71 They used a large mesh SEMS with deployment across the bifurcation.…”
mentioning
confidence: 99%